Whale vertebra from Miocene beds in Turje near Dol pri Hrastniku, Slovenia - Mikuž, Vasja (Geologija, 1998)
Examined was the whale vertebra from Badenian beds near the settlement of Turje. The vertebra is lumbal or caudal, and it belonged to an adolescent subject, most probably a whale of family Balaenopteridae.